2007
DOI: 10.1212/01.wnl.0000260963.08711.08
|View full text |Cite
|
Sign up to set email alerts
|

ATP13A2 missense mutations in juvenile parkinsonism and young onset Parkinson disease

Abstract: We confirm that ATP13A2 homozygous mutations are associated with human parkinsonism, and expand the associated genotypic and clinical spectrum, by describing a homozygous missense mutation in this gene in a patient with a phenotype milder than that initially associated with ATP13A2 mutations (Kufor-Rakeb syndrome). Our data also suggest that ATP13A2 single heterozygous mutations might be etiologically relevant for patients with YOPD and further studies of this gene in Parkinson disease are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
230
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(238 citation statements)
references
References 18 publications
7
230
1
Order By: Relevance
“…In support of this notion, a role of lysosomal dysfunction in the pathogenesis of PD, it was recently described that ATP13A2, a lysosomal type 5 p-type ATPase, is linked to an autosomal recessive form of early-onset parkinsonism with pyramidal degeneration and dementia: so-called Kufor-Rakeb syndrome (PARK9) (33). It was further shown that several missense mutations of ATP13A2 are associated with some types of juvenile and young onset PD (47). Interestingly, the current study shows that ATP13A2 was co-localized with mutant ␤-syn in lysosomal inclusions formed in cells overexpressing mutant ␤-syn (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…In support of this notion, a role of lysosomal dysfunction in the pathogenesis of PD, it was recently described that ATP13A2, a lysosomal type 5 p-type ATPase, is linked to an autosomal recessive form of early-onset parkinsonism with pyramidal degeneration and dementia: so-called Kufor-Rakeb syndrome (PARK9) (33). It was further shown that several missense mutations of ATP13A2 are associated with some types of juvenile and young onset PD (47). Interestingly, the current study shows that ATP13A2 was co-localized with mutant ␤-syn in lysosomal inclusions formed in cells overexpressing mutant ␤-syn (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…A homozygous mutation was also identified in a Japanese patient with clinical features similar to Kufor-Rakeb syndrome but later onset [245]. Mutation screening of PD cases with early onset, but otherwise no atypical signs similar to Kufor-Rakeb syndrome, showed a few other mutations, both homozygous and heterozygous [246,247]. The ATP13A2 protein is a lysosomal ATPase [179], indicating that the lysosomal degradation pathway may play a role in the pathogenesis of PD.…”
Section: Atp13a2 (Park9)mentioning
confidence: 89%
“…KRS is characterized by juvenile-onset autosomal recessive nigro-striatal-pallidal-pyramidal neurodegeneration with clinical features of Parkinson disease (PD) plus spasticity, supranuclear upgaze paresis, and dementia (1). Homozygous and heterozygous mutations in ATP13A2 are also found in patients with various parkinsonism, including juvenile parkinsonism, young-onset PD, early-onset PD, and familial PD (2)(3)(4)(5)(6)(7)(8)(9). ATP13A2 encodes a predicted lysosomal P5-type cationtransporting ATPase with multiple transmembrane domains.…”
mentioning
confidence: 99%